Structural Optimization and Comparative Analysis of B-type Metro Bogie Frame - Qingwei SONG; Chunyou GAO; Jing ZHANG; Zhuo CHEN; Wei WEI (机车电传动)
According to the service life of bogie frame of a project can not meet the operation requirements, by comparing and analyzing the time-domain and frequency-domain diagrams of line dynamic stress test data, the optimal structure scheme was put forward. The optimized structure scheme was verified by theoretical calculation, finite element analysis and actual operation line test. The stress of the key parts of the optimized structure was greatly reduced, and the equivalent stress of all measuring points was less than the standard limit of 70 MPa, which met the requirements of normal service life of vehicles.